PENGEMBANGAN VARIASI PERMAINAN BOLA BOTOL PELANGI PADA PEMBELAJARAN BOLA KECIL UNTUK SISWA KELAS IV SEKOLAH DASAR - Rachmat Nur Ichsan; I Nengah Sudjana; Fahrial Amiq (Jurnal Pendidikan Jasmani)
Abstract: Variations in bottles rainbow ball game is a game played in groups by means of small ball and bottles targets by a wide range of colors in order to attract entusiastic students to play go and the game is developing a motor movement of students, train students to work together, to make a strategy, to good sportsmanship and to fair play so that the game can be used as teacher an alternative in learning small ball for the fourth grade students Elementary School. Research procedures used are referring to books Borg & Gall which has been modified in accordance Ardhana researchers from 10 steps to 7 steps. Test data analysis in the form of a percentage. Based on the analysis of data obtained by a small group test with subject 10 students it wasobtained trial percentage of 87.97% and the percentage included in the creteria are eligible as well data analysis of test large group test with subject 30 students it was obtained a percentage of 88.70% and the percentage falls with in the creteria feasible, so we can say the product variations in bottles rainbow ball game is fit for use in the learning process.      Keywords: development, game, bottles rainbow ball, learning and small ball.Abstrak: Variasi permainan bola botol pelangi adalah permainan yang dimainkan berkelompok, dengan menggunakan sarana bola kecil dan botol sasaran yang diberi berbagai macam warna agar menarik antusias siswa untuk bermain.Tujuan dari permainan ini adalah  mengembangkan gerak motorik siswa, melatih siswa untuk bekerjasama, membuat strategi, bersikap sportif serta menerima kekalahan (fair play), sehingga permainan ini dapat dijadikan alternatif guru dalam pembelajaran bola kecil untuk, siswa kelas IV Sekolah Dasar. Prosedur penelitian yang digunakan adalah merujuk pada buku Borg&Gall yang telah dimodifikasi peneliti sesuai Ardhana dari 10 langkah menjadi 7 langkah. Teknik analisis data yang digunakan adalah analisis kualitatif dan analisis kuantitatif berupa persentase. Berdasarkan hasil analisis data uji coba kelompok kecil dengan subjek 10 siswa diperoleh persentase 87,97% dan persentase tersebut termasuk dalam kriteria layak serta hasil analisis data dari uji coba kelompok besar dengan subjek 30 siswa diperoleh persentase 88.70% dan persentase tersebut masuk dalam kriteria layak, sehingga dapat dikatakan produk variasi permainan bola botol pelangi ini layak digunakan dalam proses pembelajaranKata kunci: pengembangan, permainan, bola botol pelangi, pembelajaran dan bola kecil.